Art and suffering: a possibility to transliterate in art - Amato Mora, Pablo Bruno (2018)
The present article develops a bibliographical investigation in order to emphasize the existing relation between art and suffering, being the last one transliterated according to the expression of art. For this purpose, a biographical journey of artists including Frida Kahlo, Arthur Rimbaud, Pablo Picasso and Camille Claudel is carried out; on that basis, they were able to give form, color and letter to the pain itself, to show what the body felt, as way of creation.